Redox Control in Olefin Polymerization and Copolymerization - Chen, Min; Yang, Bangpei; Chen, Changle (Synlett, 2016)
In the field of olefin polymerization, catalyst modification remains the prevalent strategy to control the polymerization and copolymerization processes. The development of alternative strategies is, nevertheless, highly fascinating. Here, the concept of redox-controlled polymerization and its applications in the ring-opening polymerization of cyclic ester type monomers is presented. Early work on the introduction of the redox-control concept into the field of olefin polymerization is described, and our approach to address the early issues and realize redox controlled olefin polymerization and copolymerization is demonstrated. Finally, some conclusions and perspectives are discussed.1 Introduction2 The Concept of Redox Control in Polymerization3 Early Work on Redox Control in Olefin Polymerization4 Our Approach to Realize Redox-Controlled Olefin (Co)Polymerization5 Conclusions and Perspectives
Keywords: olefin polymerization; polar monomer; redox control; palladium catalysis; switchable polymerization